Himmelsbeobachtungen und deren Messung, von der Regierungszeit des Gudea von Lagash bis zum Almagest des Claudius Ptolemäus - KLEB, Jens (Historia i Świat, 2023)
The present article gives an overview on the development of the measurement and practical acquisition of circle section dimensions since the late 3rd millennium BC. In key points, the prerequisites and practical implementation for celestial observations over approx. 1500 years up to the 8th century BC are collected and analyzed, in terms of their logical requirements and connected archaeological findings. A comprehensible and unambiguous calculation is made for the celestial dimensions in cubits used from the 8th to the 2nd century BC, for which estimated values between 2.5 and 2.1 angular degrees have been determined since Kugler 1900 until to recently researchers. Therefore, for the first time, the exact transformation value is presented here. Not only the connections and the further development of this celestial measurement system are presented, but also its coherent adaptation up to the first definition and use of the angular unit measurement, which is still used today, around 200 BC. In addition, some data and their previous interpretation from various sources are put up for discussion, which even include the table of Chords, presented by Ptolemy in his Almagest and their use.